Does the Understanding of Managing Variables among Pre-Service Early Childhood Teachers Correspond to Distinct Teaching Methods in Their Future Careers? - Anastasios Zoupidis; Vassilis Tselfes; Petros Kariotoglou (MDPI AG, 2024)
This study aims to examine the views of pre-service early childhood student teachers (referred to as student teachers) regarding the potential impact of an inquiry-based science course on their intention to utilize inquiry-based learning approaches, such as the Control of Variables Strategy (CVS) method. The study comprised a preliminary phase (N = 17) and a primary phase (N = 81). The participants' level of understanding of the inquiry-based method was assessed using an open- and semi-open questionnaire. A 34-item Likert-type questionnaire was created using the Theory of Planned Behavior in the preliminary phase of the study and utilized in the primary phase to examine student teachers' intentions to include the CVS technique into their lessons. The results showed student teachers' strong intention to implement inquiry-based learning strategies, being supported by their positive estimations of managing the CVS method engagement in the classroom. However, their estimations of the significant others' opinions and the personal gain-loss balance expected from engaging with the CVS method significantly hindered their intention. Most interestingly, the results of the study suggest that the various levels of comprehension of the CVS method attained by student teachers are connected to the adoption of distinct approaches in their future teaching endeavors. In light of these results, we discuss several teaching implications.